Four ways Western Australia can improve Aboriginal heritage management - Jones, Tod; Grabasch, G. (2016)
Argues for a system of cultural heritage management that is able to cope with the recognition that Aboriginal connection and heritage is living, ongoing, and constantly around us. We propose four principles that imagine a new engagement with Aboriginal and Torres Strait Islander heritage, based on the principle of “ask first” in order to respect the guidance and wishes of Indigenous peoples .